The Christmas cookie wars : a novel - Evans, Eliza (G.P. Putnam's Sons, 2024)
"From the author of The Christmas Café, a romantic comedy about a woman who's determined to save Christmas for her sons, even if it means waging a holiday cookie war with their handsome principal...if she can resist falling in love with him."--